NEW POSSIBILITIES FOR EVALUATION OF SEVERITY AND PROGNOSIS IN PATIENTS WITH CHRONIC HEART FAILURE BASED ON N-TERMINAL PRO-BRAIN NATRIURETIC PEPTIDE PLASMA LEVEL - A. S. Galjavich; S. N. Merjasev; R. A. Galjavi; R. F. Merjaseva (Столичная издательская компания, 2016)
Aim. To study an importance of plasma N-terminal pro-brain natriuretic peptide (N-proBNP) in evaluation of severity and prognosis in patients with chronic heart failure (CHF) of ischemic genesis. Material and methods. 77 patients (60 men and 17 women; 59,4±10,7 y.o.) with CHF of ischemic genesis were included in the study. All patients had sinus rhythm and history of Q wave myocardial infarction. Standard examination was performed to all patients. Besides N-proBNP plasma level and patients yearly survival were evaluated. Results. N-proBNP plasma level had direct correlation with clinical indices (exercise tolerance, blood pressure, heart rate) and echocardiographic heart sizes. N-proBNP plasma level had relationship with prognosis of CHF patients. Baseline N-proBNP level was more than 2 times higher in died patients in comparison with survived patients. The yearly survival rate of CHF patients was 51,3% if N-proBNP level had been more than 400 fmol/ml (>15% of normal value). The clinico-laboratory index (based on N-proBNP plasma level) of severity and prognosis in CHF patients was developed. Conclusion. The clinico-laboratory index based on N-proBNP plasma level is easy to use and can improve medical practice.